2018
DOI: 10.21608/nssj.2018.30728
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Uranium Source and Its Effect on Contamination of Groundwater in El Rakaiz-El Sahu Area, Southwestern Sinai, Egypt

Abstract: The studied area has a special interest in natural resources and prospecting for radioactive minerals and also, the groundwater, which has a great value for development purpose for Bedouin. At the studied locality in El Rakaiz-El Sahu area the discover tabular fractured rock bodies host uraninite, xenotime, and iron mineralization through the fracture cutting the lower Paleozoic sandstone rocks. These occurrences of minerals concentration are interpreted to the ascending solutions contain uranium and associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Abu-Zeid et al (2016) concluded that the radioactive mineral deposits in the Adedia type section were mainly the product of epigenetic processes within which laterization played a major role. Bishr et al (2018) stated that the mineralized fault zone in the El Rakaiz-El Sahu area occurs in a large fracture system trending in a NE-SW direction.…”
mentioning
confidence: 99%
“…Abu-Zeid et al (2016) concluded that the radioactive mineral deposits in the Adedia type section were mainly the product of epigenetic processes within which laterization played a major role. Bishr et al (2018) stated that the mineralized fault zone in the El Rakaiz-El Sahu area occurs in a large fracture system trending in a NE-SW direction.…”
mentioning
confidence: 99%